Hybrid entrepreneurs as the neoteric driver of skill variety and economic prosperity - Alex Maritz; Quan Nguyen; Abu Ismail (Administrative Sciences, 2023)
Nearly a quarter of all global start-ups are founded by hybrid entrepreneurs, that is, individuals that engage in self-employment activity while simultaneously holding a primary job in wage or remuneration work. This study is the first of its kind to examine hybrid entrepreneurship in Australia using five pragmatic and embedded hybrid entrepreneur mini case studies. Aligning with human capital and skill variety theory, we adopted an interpretivist philosophical paradigm of emergent enquiry action and exploratory research. The paper explores characteristics and antecedents in the forms of the benefits and challenges associated with this increasingly prevalent form of entrepreneurship, including contextual and theoretical foundations. We provide policy and pragmatic research recommendations to enhance the development of this form of employment not only as a steppingstone to full-time self-employment but also as a driver of economic and social benefit to global societies. Furthermore, we provide inferences for future scientific studies within this domain.
Keywords: 350; hybrid entrepreneurship; self-employment; start-ups